Agronomic performance of BC3F2 aromatic rice lines derived from Inpari 32 × Merah Wangi crosses - MUHAMMAD RASSYA DHIO ANANTA; TRI AGUS SISWOYO; SHOLEH AVIVI; TRI HANDOYO; UMMI SHOLIKAH; TRI RATNASARI; AHMAD ILHAM TANZIL; WAHYU INDRA DUWI FANATA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ananta MRD, Siswoyo TA, Avivi S, Handoyo T, Sholikah U, Ratnasari T, Tanzil AI, Fanata WID. 2025. Agronomic performance of BC3F2 aromatic rice lines derived from Inpari 32 × Merah Wangi crosses. Biodiversitas 26: 6417-6426. Aroma is a key grain-quality trait that strongly influences consumer preference and market value in rice. Enhancing fragrance while maintaining high agronomic performance remains a key breeding objective. This study aimed to introgress the BADH2 aromatic allele from Merah Wangi into the high-yielding Inpari 32 background using Marker-Assisted Backcrossing (MAB), and to evaluate the resulting BC3F2 population for agronomic traits and aroma expression. A total of 98 BC3F2 individuals and both parents were assessed under field conditions. Genotypic screening using the Bradbury marker identified fourteen homozygous BADH2⁻/⁻ plants, confirming successful introgression of the recessive fragrance allele. Agronomic evaluation revealed that the BC3F2 population exhibited a stable heading date, intermediate plant architecture, and improved tillering capacity compared to its parents. Yield-related traits, including filled grain number, productive tillers, and 1000-grain weight, contributed to a higher grain yield per plant compared with both Inpari 32 and Merah Wangi. Grain-quality assessment further indicates a favorable kernel morphology, suggesting effective recombination of grain-size determinants. Organoleptic testing confirmed consistent aromatic expression across all homozygous lines, demonstrating strong agreement between molecular genotype and fragrance phenotype. Although segregation deviated from the expected 1:2:1 Mendelian ratio, the reliable identification of homozygous aromatic plants indicates that the fragrance trait was effectively fixed in this generation. Overall, the results highlight the efficiency of MAB for transferring recessive fragrance alleles into the elite rice backgrounds while maintaining desirable agronomic performance. The fourteen BC3F2 aromatic lines represent promising materials for further advancement, multilocation evaluation, and potential development of high-yielding aromatic derivatives of Inpari 32.